2016
DOI: 10.1016/j.envres.2016.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Dengue in a changing climate

Abstract: Dengue is the world's most important arboviral disease in terms of number of people affected. Over the past 50 years, incidence increased 30-fold: there were approximately 390 million infections in 2010. Globalization, trade, travel, demographic trends, and warming temperatures are associated with the recent spread of the primary vectors Aedes aegypti and Aedes albopictus and of dengue. Overall, models project that new geographic areas along the fringe of current geographic ranges for Aedes will become environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
262
0
17

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 420 publications
(282 citation statements)
references
References 39 publications
3
262
0
17
Order By: Relevance
“…We inferred that it was probably due to the climate that year, because climate significantly influences viruses, mosquitoes and hosts. A large number of studies on the effect of climate on dengue morbidity have been completed in China and abroad Cheng et al, 2016;Ebi and Nealon, 2016;Quam et al, 2016). These studies indicated a preferred temperature range for DENV reproduction from 18.0 to 33.2 °C.…”
Section: Discussionmentioning
confidence: 99%
“…We inferred that it was probably due to the climate that year, because climate significantly influences viruses, mosquitoes and hosts. A large number of studies on the effect of climate on dengue morbidity have been completed in China and abroad Cheng et al, 2016;Ebi and Nealon, 2016;Quam et al, 2016). These studies indicated a preferred temperature range for DENV reproduction from 18.0 to 33.2 °C.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has proven to be highly useful for disease prevention and has been used to forecast epidemics, which is imperative for the preparedness of health systems to cope with such outbreaks [3, 4, 7, 1219]. For example, land surface temperature and vegetation index obtained from satellite data showed significant correlation with the occurrence of sand flies in East Africa [4].…”
Section: Introductionmentioning
confidence: 99%
“…(3) Hence, even with a greater emphasis on public health controls, there will still be an increase in emerging disease events. What is of greater concern is that this may be only the beginning of observed climate-related diseases in this region and other locations.…”
mentioning
confidence: 99%